SOCIO-ECONOMIC EMPOWERMENT AND ADDITIONAL IMPACTS OF MGNREGP IN TIRUNELVELI DISTRICT - M.Sujitha; Goldagrace Duraisingh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Government of India's flagship program, the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS), aims to improve socioeconomic circumstances and livelihoods by giving rural households wage employment. This study assesses the socioeconomic, empowering, and developmental effects of MGNREGP in Tamil Nadu's Tirunelveli district. With a focus on the role of women, the study mainly examines how the program has affected rural workers' empowerment, education, health, food security, income levels, and employment creation. But the survey also points out enduring problems including corruption, poor job quality, and problems with how well the plan is being implemented. The study evaluates the effectiveness of the program and offers insights into workers' socioeconomic empowerment using statistical techniques such as percentage analysis, regression analysis, and the Garrett ranking approach. The results indicate that although MGNREGP has made a substantial contribution to empowerment and poverty alleviation, there is still room for development, especially in the areas of transparency, work quality, and the sustainability of rural assets. To maximise the program's efficacy, the report suggests actions like improved training, monitoring, gender-focused legislation, and awareness campaigns. These suggestions are meant to help stakeholders, local government representatives, and legislators increase the effectiveness of MGNREGP in rural areas.